PENINGKATAN HASIL BELAJAR ROLL DEPAN DAN KEPERCAYAAN DIRI MELALUI GAME-BASED LEARNING PADA SISWA KELAS IV SD ISLAM TERPADU BAITURRAHMAN - Joko Priyono; Mashud Mashud (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study aimed to improve students’ forward roll learning outcomes and self-confidence through the implementation of Game-Based Learning integrated with a progressive learning approach in physical education classes. The study employed a Classroom Action Research (CAR) design conducted in two cycles, consisting of the stages of planning, action, observation, and reflection. The participants were 32 fourth-grade elementary school students. Data were collected using students’ self-confidence observation sheets, teacher activity observation sheets, student activity observation sheets, and learning documentation. Data were analyzed using both quantitative and qualitative descriptive techniques through percentage calculations and reflective evaluations in each cycle. The indicators of self-confidence included willingness to participate, courage to express opinions, readiness to try new skills, decision-making ability, and confidence in one's own abilities. The findings revealed that the implementation of Game-Based Learning with a progressive learning approach gradually improved both students’ learning outcomes and self-confidence. The percentage of students achieving learning mastery was 31.3% in the pre-cycle stage, increasing to 37.5% in Cycle I Meeting 1 and 59.4% in Meeting 2. In Cycle II, learning mastery improved significantly to 87.5%. Similarly, students’ self-confidence showed substantial improvement, increasing from 31.3% in the pre-cycle stage to 56.3% in Cycle I and reaching 78.1% in Cycle II. These findings indicate that progressively implemented game-based learning creates an active, enjoyable, and meaningful learning environment that enhances both motor skill performance and students’ self-confidence. Therefore, Game-Based Learning based on a progressive learning approach can serve as an effective alternative instructional model for improving the quality of physical education learning in elementary schools.